Design de embalagens para empresa de cosméticos - Sfredo, Alyne Ricardo (2013)
This project intents to develop a packaging line of cosmetics for the company “Premisse” and contribute to the discussions about the packaging design. Due to this bibliographies of involved areas were studied such as the history of packaging, plastics and manufacturing processes. Also were conducted analyses of competitives brands interviews with the company and with consumers in order to add knowledge and to understand the principals and the most explored elements in packaging design. After the theoretical part was created the concept for the project and developed a line of cosmetic packaging to the company “Premisse” called Personal Care” composed by plastic, label and promotional kit.